2016
DOI: 10.4238/gmr.15038206
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gene methylation in human papillomavirus associated-head and neck squamous cell carcinoma

Abstract: ABSTRACT. Head and neck squamous cell carcinoma (HNSCC) has become one of the most common forms of cancer worldwide. Hypermethylation-induced silencing of tumor-associated gene has been proposed as an important cofactor in cancer pathology. This paper aimed to characterize the gene methylation patterns in human papillomavirus (HPV) associated-HNSCC. TIMP3 and APC methylation status in neoplastic (N = 92) and non-neoplastic tissues (N = 92) of HNSCC as well as their association with HPV infection were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…We found an association between the absence of TIMP3 methylation and patients with clinically negative lymph nodes at diagnosis. A similar association was reported for HPV‐positive head and neck 19 and gastric cancer 20 ; our group also demonstrated that TIMP3 hypermethylation in HNC tumor tissue was associated with the development of second primary tumors, 16 and TIMP3 methylation in salivary rinse as an independent prognostic factor for HNC patients 15 . Although we were not able to find an association with survival rates, probably due to the small sample size, TIMP3 methylation is undoubtedly relevant in HNC carcinogenesis.…”
Section: Discussionsupporting
confidence: 85%
“…We found an association between the absence of TIMP3 methylation and patients with clinically negative lymph nodes at diagnosis. A similar association was reported for HPV‐positive head and neck 19 and gastric cancer 20 ; our group also demonstrated that TIMP3 hypermethylation in HNC tumor tissue was associated with the development of second primary tumors, 16 and TIMP3 methylation in salivary rinse as an independent prognostic factor for HNC patients 15 . Although we were not able to find an association with survival rates, probably due to the small sample size, TIMP3 methylation is undoubtedly relevant in HNC carcinogenesis.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have detected M TIMP3 more frequently in tumor tissue of patients with early-stage (I/II) HNSCC compared with healthy saliva samples ( 113 , 114 ) but they did not find a clinical association with cancer. A study characterizing the epigenome in HPV + patients with HNSCC showed that aberrant TIMP3 was predominant in HPV + patients ( 115 ). The authors showed that M TIMP3 was associated with positive lymph node spread, and consequently, with a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%